2013
DOI: 10.1007/s10404-013-1295-5
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput microcapillary pump with efficient integrated low aspect ratio micropillars

Abstract: Prediction and reduction of pressure drop and resistance flow in micropillar arrays are important for the design of microfluidic circuits used in different lab-on-a-chip and biomedical applications. In this work, a diamond microchannel-integrated micropillar pump (dMIMP) with a resistance flow 35.5 % lower than a circular-based micropillar pump (cMIMP) has been developed via the optimization of the fluid dynamic behavior of different pillar shapes in a low aspect ratio (H/D ranged from 0.06 to 0.2) integrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 also paves the path for collecting the separated plasma in the top part using multiple collected channels due to a filled distributed area with blood plasma. Its design is the result of our previous work for developing a high-throughput microcapillary pump with efficient integrated low aspect ratio micropillars [40]. The obtained results indicated that the diamond pillar array presents the minimum resistance flow compared to the other pillar shapes.…”
Section: Design and Principle Of The Self-driven Microfluidic Devicementioning
confidence: 99%
See 1 more Smart Citation
“…3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 also paves the path for collecting the separated plasma in the top part using multiple collected channels due to a filled distributed area with blood plasma. Its design is the result of our previous work for developing a high-throughput microcapillary pump with efficient integrated low aspect ratio micropillars [40]. The obtained results indicated that the diamond pillar array presents the minimum resistance flow compared to the other pillar shapes.…”
Section: Design and Principle Of The Self-driven Microfluidic Devicementioning
confidence: 99%
“…To reach this aim, according to Madadi et al [40]; the diamond post shape with increased side distance between pillars is the most efficient design for minimizing the MIMP channel flow resistance and it can be calculated through where µ is the fluid viscosity, L is the length of microchannel, w is the half depth of microchannel, H is the height of microchannel and ε is the porosity [40]. Since the fluid and the height of the channel are fixed, we have maximized the porosity to achieve a manufacturable device.…”
Section: Design and Principle Of The Self-driven Microfluidic Devicementioning
confidence: 99%
“…In the work of Madadi et al (2014), an extensive investigation of both the micropillar geometry and array topology on the hydraulic resistance was presented. The authors examined a large variety of micropillar shapes and offered a detailed comparison between these, describing optimal architectures to ensure minimum flow resistances.…”
Section: Pcb-based Micropillar Designsmentioning
confidence: 99%
“…Equations (1) and (2) define the relation between the design parameters (MFS, FD, D, SD and LD) of the diamond and circular architectures, respectively, derived from the experimental results in micropillar capillary pump flow rate performance of Madadi et al (2014).…”
Section: Pcb-based Micropillar Designsmentioning
confidence: 99%
See 1 more Smart Citation